Flight gate scheduling: State-of-the-art and recent developments - Ulrich Dorndorf; Andreas Drexl; Yury Nikulin; Erwin Pesch (Universität Kiel, Institut für Betriebswirtschaftslehre; ZBW – Leibniz Information Centre for Economics, 2005)
This paper surveys a large variety of mathematical models and up-to-date solution techniques developed for solving a general flight gate scheduling problem that deals with assigning different aircraft activities (arrival, departure and intermediate parking) to distinct aircraft stands or gates. The aim of the work is both to present various models and solution techniques which are available in nowadays literature and to give a general idea about new open problems that arise in practise. We restrict the scope of the paper to flight gate management without touching scheduling of ground handling operations.s
Keywords: 650; flight gate scheduling; assignment of aircraft activities to terminals; survey of models and algorithm; Luftverkehr; Flughafen; Scheduling-Verfahren; Heuristik; Theorie